2023
DOI: 10.1002/prca.202200114
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and validation of serum glycoprotein biomarkers for high grade serous ovarian cancer

Abstract: Purpose This study aimed to identify serum glycoprotein biomarkers for early detection of high‐grade serous ovarian cancer (HGSOC), the most common and aggressive histotype of ovarian cancer. Experimental design The glycoproteomics pipeline lectin magnetic bead array (LeMBA)‐mass spectrometry (MS) was used in age‐matched case‐control serum samples. Clinical samples collected at diagnosis were divided into discovery (n = 30) and validation (n = 98) sets. We also analysed a set of preclinical sera (n = 30) colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…A promising clinical application of targeted MS is the identification and quantification of peptide or protein cancer biomarkers [ 14 21 ]. Recent research has identified serum glycoprotein HGSOC biomarkers using MRM [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…A promising clinical application of targeted MS is the identification and quantification of peptide or protein cancer biomarkers [ 14 21 ]. Recent research has identified serum glycoprotein HGSOC biomarkers using MRM [ 22 ].…”
Section: Introductionmentioning
confidence: 99%